Fixed points on trivial surface bundles over a connected CW-complex - Gonçalves, Daciberg Lima; Libardi, Alice Kimie Miwa [UNESP]; Penteado, Dirceu; Vieira, João Peres [UNESP] (My University, 2015)
The main purpose of this work is to study fixed points of fibre-preserving maps over a connected CW-complex B on the trivial surface bundles B×S where S is a closed surface of negative Euler characteristic. The case where B = S1 and S is equal to S2, i.e., the closed orientable surface of genus 2, is already known. We classify all such maps that can be deformed fibrewise to a fixed point free map.
Keywords: Braids; Fibre bundle; Fibrewise maps and homotopy; Fixed point; Surface